Culture strategy as a modulator of target assessments: Functionality of suspension versus hanging drop‐derived choriocarcinoma spheroids as in vitro model of embryo implantation. Issue 9 (26th April 2021) - Kazemi, Mahsa; Jajarmi, Vahid; Nazarian, Hamid; Ghaffari Novin, Marefat; Salehpour, Saghar; Piryaei, Abbas; Heidari Khoei, Heidar; Choobineh, Hamid; Abdollahifar, Mohammad Amin; Haji Molla Hoseini, Mostafa; Heidari, Mohammad Hasan
Abstract: The choriocarcinoma spheroid model has been amply applied to study the underlying molecular mechanism of implantation. Reproducibility and functionality of spheroid tumor models were addressed precisely. To mimic embryo‐endometrium crosstalk, no functional characteristics of spheroids have been provided based on culture strategies. In this study, choriocarcinoma spheroids were provided as suspension culture (SC) or hanging drop culture (HDC). Primary assessments were performed based on morphology, cellular density, and hormonal secretion. Spheroid‐endometrial cross talk was assessed as coculture procedures. Further, alkaline phosphatase (ALP) activity and expression of genes involved in attachment, invasion, and inducing migration were quantified. We found HDC spheroids provided a homogenous‐shaped aggregate with a high grade of viability, cellular integration, hormonal secretion, and the dominant role of WNTs expression in their microarchitecture. SC spheroids showed a higher level of ALP activity and the expression of integrated genes in modulating attachment, invasion, and migration abilities. Spheroid confrontation assays clearly clarified the superiority of SC spheroids to crosstalk with epithelial and stromal cells of endometrium in addition to motivating an ideal endometrial response. Conclusively, culture strategies by affecting various molecular signaling pathways should be chosen precisely according to specific target assessments. Specifically, SC assumed as an ideal model in spheroid‐endometrial cross talk.